A REVIEW FROM HISTORICAL TO CURRENT-CELASTRUS PANICULATUS - SHARMA, GANESH N.; KAUR, HARJINDER; SHRIVASTAVA, BIRENDRA; ARORA, SATISH CHANDER (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Celastrus paniculatus is commonly known as “Malkangani”, widely distributed in the Maldives, Australia, China, Cambodia, Malaysia, Taiwan, Nepal, Thailand as well as in the Pacific Islands and all over India mainly Maharashtra, Orissa and Andaman and Nicobar group of Islands on an altitude of 1800m. It climbs up to over 10m. The leaves are ovate or elliptic in shape with dentate margin. Seeds are ellipsoid or ovoid, yellowish-brown in color and grow inside the capsules. Celastrus paniculatus (Malkangni) is used in Ayurveda as a nervine tonic, tranquilizer and diuretic and in rheumatism, gout, leprosy and asthma. Different Parts of Celastrus paniculatus after extraction and fractionation give different active constituents such as sesquiterpene esters-malkanguinol, malkangunin, sesquiterpene alkaloids-celapanin, celapanigin, alkaloids-celastrine, paniculatine, fatty acids-oleic acid, palmittic acid, linoleic acid and stearic acid, crystalline substance tetracasanol and sterol. Different pharmacological activities are anti-rheumatic, anti-fungal, nootropic activity, antimalarial activity, anti spermatogenic effect, anti-anxiety and anti-atherosclerotic effect. In the present review, our target is to search, bring together and compile the data of Celastrus paniculatus, which have less side effects and very valuable for the treatment of rheumatism. Related information is procured from various scientific publications using online, seek out engines such as Google scholar, Pubmed and Science Direct. A total of 200 articles was reviewed out of which 55 articles are selected to review for the description of the plant, parts used, chemical constituents, traditional uses and for reported activities.